What is the source of L1 attrition? The effect of recent L1 re-exposure on Spanish speakers under L1 attrition*. Issue 3 (29th April 2015) - CHAMORRO, GLORIA; SORACE, ANTONELLA; STURT, PATRICK
Abstract : The recent hypothesis that L1 attrition affects the ability to process interface structures but not knowledge representations (Sorace, 2011) is tested by investigating the effects of recent L1 re-exposure on antecedent preferences for Spanish pronominal subjects, using offline judgements and online eye-tracking measures. Participants included a group of native Spanish speakers experiencing L1 attrition ('attriters'), a second group of attriters exposed exclusively to Spanish before they were tested ('re-exposed'), and a control group of Spanish monolinguals. The judgement data shows no significant differences between the groups. Moreover, the monolingual and re-exposed groups are not significantly different from each other in the eye-tracking data. The results of this novel manipulation indicate that attrition effects decrease due to L1 re-exposure, and that bilinguals are sensitive to input changes. Taken together, the findings suggest that attrition affects online sensitivity with interface structures rather than causing a permanent change in speakers' L1 knowledge representations.